2012
DOI: 10.1109/ms.2011.92
|View full text |Cite
|
Sign up to set email alerts
|

The Success Factors Powering Industry-Academia Collaboration

Abstract: Collaboration between industry and academia supports improvement and innovation in industry and helps to ensure industrial relevance in academic research. This paper presents an exploratory study of factors for successful collaboration between industry and academia. A survey was designed for data collection and was firstly conducted in Sweden then replicated in Australia. The context for the two studies is different thus forming a starting point for potential generalizations in the future. From the two studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
3

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(91 citation statements)
references
References 3 publications
4
86
0
1
Order By: Relevance
“…Although companies in emerging industries may be more likely to collaborate with universities for research and development than in mature industries 11 , we saw firms in both types of industries benefit from ERC collaboration. Finally, our research also supports extant recommendations to improve industry-university tiesmaintaining a focus on building stakeholder commitment, in part through a designated liaison responsible for relationship management 80 .…”
Section: Boundary-breaking Collaborationsupporting
confidence: 75%
See 1 more Smart Citation
“…Although companies in emerging industries may be more likely to collaborate with universities for research and development than in mature industries 11 , we saw firms in both types of industries benefit from ERC collaboration. Finally, our research also supports extant recommendations to improve industry-university tiesmaintaining a focus on building stakeholder commitment, in part through a designated liaison responsible for relationship management 80 .…”
Section: Boundary-breaking Collaborationsupporting
confidence: 75%
“…65,82 . To achieve researcher participation in commercialization, it may be necessary to broaden the traditional academic criteria used in annual performance reviews and tenure and promotion decisions beyond can help improve relationships between involved parties 80 , and we suggest giving universityindustry liaisons responsibility throughout the commercialization process. In our research, we found that the most successful ILOs served both as "evangelists of the value of technology commercialization and as providers of resources to researchers, the tech transfer office, and industry to coordinate effective collaboration among all participants" (p. 104) 85 .…”
Section: Orchestrated Commercializationmentioning
confidence: 99%
“…This model represents a very close collaboration between industry and academia. Despite these insights as well as documentation of success factors for collaboration between industry and academia [9] and [10], it is still hard to build a sustainable long-term research collaboration between industry and academia.…”
Section: Related Workmentioning
confidence: 99%
“…The company is collaborating with an academic partner, and hence ask about their advice based on the available evidence in literature. We have received questions regarding research evidence related to other topics in our close industrial collaboration [18]. Given that they perceive that inspections are not very domain dependent, they do not only want findings from their own domain.…”
Section: Illustration Of Modelmentioning
confidence: 99%